Effects of Stress on Native Speaker Evaluations of a Japanese English Learner's Pronunciation - KATAYAMA, Tamami (HELES JOURNAL, 2009)
This study investigates the use that second language learners make of stress features in English, and tests which features affect overall comprehensibility as evaluated by native speakers of the language (English). A preliminary study set out to specify the suprasegmental feature (or features) of L2 speech that affect(s) the ratings awarded by native speakers. Four native English-speaking instructors rated the pronunciation of sixteen L2 English speakers of Japanese with respect to segmentals, intonation, and rhythm, after which the best and the poorest pronunciation were selected and analyzed with a speech analyzer. The results revealed that although the Japanese speakers attempted to use speech accents, these were produced in a way that native speakers of English were not always able to distinguish. The audio sample of the poorest pronunciation was then adjudicated in terms of the pitch, vowel duration, and intensity of the stressed syllables. One hundred native English speakers (NES) and 20 L2-fluent, non-native English teachers of Japanese speakers (ETJ) rated the comprehensibility of both the original L2 speech samples and their manipulated versions. The results of the Wilcoxon signed−rank tests showed that, for both groups, the L2 samples with both enhanced pitch and duration were significantly less comprehensible than the unenhanced originals (pitch: NES: z = −3.93, p<.01; ETJ: z=−3.56, p<.01; duration: NES: z=−1.96, p=.05; ETJ: z=−2.08, p<.05) ETJ also rated the enhanced-intensity files as less comprehensible than the originals, although the difference was not significant (p=0.56). In contrast, NES rated the enhanced-intensity files higher in comprehensibility, although the difference was again not significant (p=0.39). This study confirms (what ordinary experience suggests) that the means by which Japanese English learners express stress can affect native English speakers find that the comprehensibility of L2 pronunciation is likely to improve when stresses syllables are made louder